Chronic Inflammatory Changes In Esophageal Mucosa of Albino Rats Following Prolonged Intake of Carbonated Drinks. - Muhammad Asif; Ashhad Mazhar; Naila Parveen; Sara Farhan; Lubna Riaz; Riaz Ahmed Shahid (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Abstract Background: Carbonated beverages include soft drinks or sodas which contain carbondioxide and that when ingested for prolonged period of time lowers the intra-esophageal pH and can lead to histopathological changes in the mucosa. Objective: To study the effects of prolonged intake of carbonated drinks on the oesophagus of albino rats. Method: This experimental study was carried out at Shaheed Mohtarma Benazir Bhutto Medical College for a period of six months. Seventy five rats of wistar strain (gender non specific) were divided into 'control groups 'A1 n=10, A2 n=10, A3 n=10 & 'exposed groups' B n=15, C n=15 and D n=15.The controls and the exposed animals were fed the same balanced diet, prepared at the lab's kitchen. The fluid intake of exposed animals was restricted to carbonated drinks only, whereas, the controls were fed water.At the end of the first, third and sixth months, groups A1&B, A2&C and A3&D were sacrificed and histological section of oesophagus were obtained for histomorphological studies. Results: On micrometry, width of the oesophagus of the exposed animals for one month;Group B was higher (17.87) than those of Group A1 (5.70). Those rats sacrificed at the end of the third month; Group C had significantly enlarged wall thickness of the oesophagus compared to A2 group. The average oesophageal wall thickness 13.60?m was found to be more in the exposed group 'D', as compared to 4.50?m measured in Control Group A3 (p<0.01). Conclusion: Prolonged consumption of carbonated drinks resulted in gross and histomorphological changes in the esophageal mucosa. The results of this research will help provide awareness to the general public of the adverse effects afflicted by these beverages.